Eksistensi Bahasa Indonesia sebagai Identitas Nasional di Tengah Arus Konten Global Berbahasa Inggris - Glori Meilani Germiana Tolan; Dhe Angel Pandie; Servulus Mariansa Hibur; Paselia Remasti Nati; Alfret Benu; Qurrata'ain (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The increasingly rapid development of globalization and digital technology has increased the intensity of Generation Z's exposure to various global English-language content through social media, digital platforms, and international information sources, thus influencing communication patterns and language use in everyday life and posing challenges to the existence of Indonesian as a national identity, a symbol of national identity, and a unifying tool for Indonesian society amidst the currents of global cultural change